Lietuvių ir slavų kalbų sąveika vilniškių tarmės rytiniuose pakraščiuose (Adutiškio apylinkių duomenys) - Urbanavičienė, Jolita (Baltistica, 2006)
PERIPHERIES OF THE VILNIUS’ DIALECT (DATA FROM THE ENVIRONS OF ADUTIŠKIS)The object of this article – two small unites (of Adutiškis and Svirkos) of the eastern Vilnius’ highlanders’ subdialect that have active contact with the Belarusian, the Russian and the Polish. We analyze the process of interaction of these languages and the changes of their status in society during the 20th century. The impact of Slavonic languages on the Lithuanian subdialects is analyzed on the bases of linguistic facts taken from bilingual informants. We make the conclusion that the processes of divergence in these peripheral areas are stronger than in the central dialects. The language of a bilingual person presents non only innovations, but also the most well conserved relics. The major changes are noticed in those layers of the language where both languages end up being used at the same time (phonetics). The inflexion is the most stable part of the grammar.
Keywords: lietuvių - slavų; vilniškiai